Game Education (Media Interaktif Mengenalkan Ibu Kota Provinsi Berbasis Android) Menggunakan Unity - Bagas Prayoga; Khairunnisa; Nur Wulan (Universitas Harapan Medan, 2021)
Currently Indonesia is officially divided into 34 provinces and each province has a capital city. Some children, especially elementary school level, still find it difficult to recognize the names of the capitals in each province in Indonesia. One of the reasons is because during the learning process at school, children still use books and teacher guidance so that it does not attract the attention of children to learn to recognize the names of capital cities in Indonesia. With interactive multimedia, children no longer feel bored in learning to recognize the names of capital cities in Indonesia. This research will produce an android-based application in recognizing the names of provincial capital cities in Indonesia. The purpose of this application is to make basic learning about the introduction of provincial capitals interesting and produce interactive media in introducing provincial capitals. This application is built using the C# programming language and Unity 3D software.